Dispersed endogenous core-shell hybrid dual-phase reinforced amorphous composite material and preparation method thereof

By introducing metal tin into the copper-zirconium-based amorphous composite material and refining the Ta-rich phase by using dealloy reaction, a uniformly distributed Ta-rich phase-B2-phase core-shell hybrid biphasic structure was prepared, which solved the problems of coarse B2 phase size and martensite phase transformation, and improved the mechanical properties of the material.

CN116200685BActive Publication Date: 2025-04-11HUAZHONG UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211725871.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-04-11
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

In the existing copper-zirconium amorphous composite materials, the B2 phase is coarse and difficult to disperse and distribute, and martensite phase transition is prone to occur during cooling, resulting in insufficient mechanical properties such as low plastic strain of the composite materials.

Method used

The thermal stability of the B2 phase is improved by introducing metal tin into the matrix material, and the composite process is designed using the dealloyment reaction in the metal melt to refine the size of the Ta-rich phase to prepare a uniformly dispersed Ta-rich phase-B2 phase core-shell hybrid biphasic structure reinforced amorphous composite materials.

Benefits of technology

The uniform distribution and thermal stability of the B2 phase are achieved, the martensite phase transformation is avoided, and the fracture strength and plastic deformation ability of the composite material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116200685B_ABST
    Figure CN116200685B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of copper-zirconium-based amorphous composite materials, and more specifically, to a dispersed endogenous core-shell hybrid dual-phase reinforced amorphous composite material and a preparation method thereof. The dispersed core-shell hybrid dual-phase reinforced amorphous composite material provided by the present invention has a chemical composition expression of Zr a Cu b Al c Sn d Ta e , wherein 40≤a≤50, 40≤b≤50, 4≤c≤10, 0.2≤d≤0.8, 3.0≤e≤7.0; and a+b+c+d+e=100; the matrix of the composite material is a copper-zirconium-based amorphous alloy, and its reinforcement phase is a hybrid dual phase with a core-shell structure. By introducing metallic tin into the alloy material and designing a composite process based on the dealloying reaction in the metal melt, a uniformly dispersed Ta-rich phase-B2 phase core-shell hybrid dual phase structure reinforced amorphous composite material is prepared, which significantly improves its mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of copper-zirconium based amorphous composite materials, and more specifically, relates to a dispersed endogenous core-shell hybrid dual-phase reinforced amorphous composite material and a preparation method thereof. Background Art

[0002] Unlike traditional crystalline alloys, amorphous alloys obtained by rapid cooling retain the characteristics of short-range order and long-range disorder of the atomic arrangement inside the liquid metal. Based on the above atomic arrangement, there are no defects such as grain boundaries and dislocations inside the amorphous alloy, so it exhibits high strength, high hardness, and large elastic limit performance characteristics that are superior to traditional crystalline alloys. However, the deformation of amorphous alloys is concentrated in local narrow shear bands, which causes the local temperature to rise and soften, and quickly lose stability and transform into cracks. Therefore, most amorphous alloys exhibit room temperature brittle fracture characteristics, which is not conducive to their practical application. Introducing a crystalline second phase into the amorphous matrix can effectively alleviate the localized deformation characteristics, promote the proliferation of shear bands, and make the deformation more evenly distributed in multiple shear bands, which can effectively improve the room temperature plasticity of amorphous alloys. There are two main methods for manufacturing bulk amorphous composites, namely in-situ self-generation and direct addition. The process design of in-situ self-generation of copper-zirconium-based amorphous composites is difficult, and most current research focuses on the direct addition method. However, the direct addition method easily forms an oxide layer or interface layer between the second phase and the matrix, and the second phase is difficult to disperse evenly, so the improvement of mechanical properties such as strength and plasticity is very limited.

[0003] In recent years, in-situ self-generated B2-CuZr phase has been found in some copper-zirconium-based amorphous alloys. It can not only inhibit the rapid expansion of the alloy matrix shear band during deformation, but also undergo stress-induced martensitic transformation to produce obvious work hardening behavior, which provides a new way to improve the room temperature brittleness of amorphous alloys and expand the application prospects of amorphous alloys. However, when preparing B2-CuZr phase-reinforced copper-zirconium-based amorphous composites, since the reinforcing phase is precipitated in-situ during the cooling process, its content is high and it is easy to connect with each other, resulting in coarse size and uneven distribution, making it difficult to achieve the expected reinforcement effect and comprehensive mechanical properties of the composite material. In order to obtain a uniformly dispersed B2-CuZr phase, the researchers proposed to use the heterogeneous nucleation method to introduce the heterogeneous nucleation substrate of the B2 phase, so that a high melting point phase is first precipitated from the melt during the cooling process, and then this high melting point phase is used as the heterogeneous nucleation substrate of the B2 phase to promote the uniform precipitation of the B2 phase.

[0004] Patent document CN113322422A discloses a hybrid phase-enhanced zirconium-based amorphous composite material and a preparation method thereof, generating a core-shell hybrid phase structure with a Ta-rich phase as the core phase, B2-CuZr and B19'-CuZr phases as the shell phases, rather than an ideal structure in which a single B2 phase encapsulates a Ta-rich phase. This is because the master alloy smelting method is arc smelting, and the smelting temperature is high and not easy to control, resulting in a coarse size of the nucleation substrate phase (Ta-rich phase) precipitated in situ, causing the core-shell enhanced structure to be unable to be dispersed. At the same time, due to the large difference in thermal expansion coefficient between the Ta-rich phase and the B2-CuZr phase, the B2-CuZr phase is affected by residual thermal stress during the cooling process and undergoes martensitic transformation to form the B19'-CuZr phase, resulting in a weakening of the work hardening enhancement effect during the actual application of the composite material, limiting the further improvement of the comprehensive mechanical properties of the composite material. Summary of the invention

[0005] In view of the defects of the prior art, the present invention provides a dispersed endogenous core-shell hybrid dual-phase reinforced amorphous composite material and a preparation method thereof, which improves the thermal stability of the B2 phase by introducing metallic tin into the matrix material, and inhibits the martensitic phase transformation during the cooling process. At the same time, a composite process is designed based on the dealloying reaction in the metal melt, and the size of the Ta-rich phase is further refined to prepare a uniformly dispersed Ta-rich phase-B2 phase core-shell hybrid dual-phase structure reinforced amorphous composite material, aiming to solve the disadvantages of the existing B2 phase reinforced amorphous composite material that the B2 phase is coarse in size, difficult to disperse and distribute, and prone to martensitic phase transformation during the cooling process, resulting in insufficient mechanical properties such as low plastic strain of the composite material.

[0006] To achieve the above object, the present invention provides a dispersed core-shell hybrid dual-phase reinforced amorphous composite material, the chemical composition of which is Zr a Cu b Al c Sn d Ta e , where 40≤a≤50, 40≤b≤50, 4≤c≤10, 0.2≤d≤0.8, 3.0≤e≤7.0; and a+b+c+d+e=100;

[0007] The matrix of the composite material is a copper-zirconium-based amorphous alloy, and its reinforcing phase is a mixed dual phase with a core-shell structure, wherein the core phase in the mixed dual phase with the core-shell structure is a dispersed Ta-rich phase, and the shell phase is a B2 phase generated around the Ta-rich phase, and the mixed dual phase with the core-shell structure is dispersed in the matrix.

[0008] Preferably, the chemical composition expression of the amorphous composite material is Zr a Cu b Al c Sn dTa e , among which, 42.0≤a≤46.5, 42.0≤b≤46.5, 4.8≤c≤8.2, 0.4≤d≤0.6, 3.0≤e≤7.0; and a+b+c+d+e=100.

[0009] According to another aspect of the present invention, there is provided a method for preparing the dispersed core-shell hybrid dual-phase reinforced amorphous composite material, comprising the following steps:

[0010] S1. According to the atomic percentage in the chemical composition of the amorphous composite material, weigh the corresponding mass of Zr, Ta, Cu, Al and Sn raw materials; mix and melt the Zr and Ta raw materials, and obtain a Zr-Ta pre-alloy after cooling; mix and melt the Cu, Al and Sn raw materials, and obtain a Cu-Al-Sn pre-alloy after cooling;

[0011] S2, mixing the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy and then induction melting to obtain a semi-solid melt, and then casting to obtain a Zr-Cu-Al-Sn-Ta master alloy ingot;

[0012] S3, spray-casting the master alloy in step S2 into a copper mold to obtain an amorphous composite material with a matrix of a copper-zirconium-based amorphous alloy and a reinforcement phase of a dispersed core-shell hybrid dual-phase reinforcement structure of a Ta-rich phase-B2 phase;

[0013] Among them, in the induction melting process described in step S2, the Cu-Al-Sn pre-alloy will first melt to obtain a Cu-Al-Sn melt, and the Zr-Ta pre-alloy ingot will be immersed in the Cu-Al-Sn melt. Since the mixing enthalpy of Ta and the Cu-Al-Sn melt is positive, and the mixing enthalpy of Zr and the melt is negative, the Zr in the Zr-Ta pre-alloy will undergo a dealloying reaction in the metal melt and selectively dissolve into the Cu-Al-Sn melt to generate a Zr-Cu-Al-Sn matrix melt, the melt composition is the same as the target melt composition, and the B2 phase can be precipitated in situ during the spray casting process described in step S3; at the same time, the remaining Ta in the Zr-Ta pre-alloy can form a dispersed fine Ta phase through surface diffusion.

[0014] Preferably, in step S1, Zr and Ta raw materials are mixed and then subjected to vacuum arc melting, and Zr-Ta pre-alloy is obtained after cooling; Cu, Al and Sn raw materials are mixed and then subjected to vacuum arc melting, and Cu-Al-Sn pre-alloy is obtained after cooling.

[0015] Preferably, the Zr and Ta raw materials are mixed and then subjected to vacuum arc melting. Considering the high melting point of the Ta element, the arc melting temperature is 3200K~3800K; the Cu, Al and Sn raw materials are mixed and then subjected to vacuum arc melting. Considering the low boiling point of the Sn element, the arc melting temperature is 1200K~1500K.

[0016] Preferably, when vacuum melting Zr, Ta raw materials and Cu, Al, Sn raw materials are respectively carried out, the vacuum arc melting process is repeated at least 4 times, and each melting is maintained for 3min to 5min after the charge is completely melted, and then the alloy is turned over after cooling for the next melting.

[0017] Preferably, in step S2, the induction melting is specifically performed as follows: placing the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy into a ceramic crucible at the same time, performing vacuum induction melting, and pouring the final melt into a mold by tilt casting to obtain a master alloy.

[0018] Preferably, the temperature of the vacuum induction melting is 1250K to 1500K, the time is 2 to 5 minutes, more preferably 2 to 4 minutes; the vacuum degree during the vacuum induction melting is 3×10 -3 Pa~5×10 -3 Pa.

[0019] Preferably, step S3 specifically comprises: crushing the Zr-Cu-Al-Sn-Ta master alloy ingot and placing it into a quartz tube for spray casting, performing vacuum induction melting, and spray casting through a copper mold after melting to obtain a copper-zirconium based amorphous composite material.

[0020] In general, the above technical solution conceived by the present invention has the following advantages compared with the prior art:

[0021] Beneficial effects:

[0022] (1) The present invention optimizes the composition design and preparation process of the B2 phase-reinforced copper-zirconium-based amorphous composite material, proposes a strategy for refining the heterogeneous nucleation base phase (i.e., core phase) based on the dealloying reaction in the metal melt, further optimizes the distribution and size of the B2 phase, and obtains a dispersed and finely distributed core-shell dual-phase hybrid reinforcement structure. First, the Zr-Ta pre-alloy is prepared by arc melting at a relatively high melting temperature, and then induction melting is performed together with the Cu-Al-Sn pre-alloy, so that the Zr element in the Zr-Ta pre-alloy is selectively dissolved into the melt to form a target Zr-Cu-Al-Sn amorphous matrix component with excellent amorphous forming ability, and the Ta-rich phase is dispersed therein. In the subsequent spray-casting process, the Ta-rich phase serves as the heterogeneous nucleation base of the B2 phase, forming a core-shell dual-phase hybrid reinforcement structure with the Ta-rich phase as the core phase and the B2 phase as the shell phase, refining the size of the B2 phase and promoting the uniform precipitation of the B2 phase. The Ta-rich phase formed by the dealloying process is small in size, thus avoiding the problem of phase transformation and decomposition of the B2 phase caused by the coarse Ta-rich phase. The composite material obtained by the present invention exhibits excellent fracture strength and plastic deformation ability.

[0023] (2) In order to make the Ta-rich phase fine and dispersed, the present invention strictly controls the dealloying reaction temperature and time to avoid the coarsening or incomplete reaction of the Ta-rich phase. The fine and dispersed Ta-rich phase can not only further promote the heterogeneous nucleation of the B2 phase, refine the size of the B2 phase, and homogenize the distribution of the B2 phase. At the same time, the fine Ta-rich phase can also reduce the degree of thermal mismatch at the interface between it and the B2 phase, avoiding the martensitic transformation of the B2 phase under the influence of thermal stress or residual heat, and failing to obtain the target dual-phase enhanced structure.

[0024] (3) The reinforcing phase in the present invention is introduced by an in-situ self-generation method, and there is no oxide layer or interface layer between the matrix and the reinforcing phase, and the reinforcing phase is uniformly dispersed in the matrix. It has the advantages of simple operation process, low cost, and excellent reinforcement effect, and can promote the application of amorphous alloy materials.

[0025] (4) The preparation method of the mixed phase reinforced copper-zirconium based amorphous composite material provided by the present invention flexibly selects the alloy melting method, and arc melts the Zr-Ta and Cu-Al-Sn pre-alloyed raw materials to reduce the volatilization of elements and obtain a uniform pre-alloyed ingot; since the controllable temperature is lower, the master alloy is prepared by induction melting of Zr-Ta and Cu-Al-Sn, and the dealloying reaction in the metal melt is introduced to obtain an amorphous composite material with excellent comprehensive mechanical properties at room temperature.

[0026] (5) The present invention improves the thermal stability of the B2 phase by introducing metallic tin into the matrix material, thereby inhibiting the martensitic phase transformation during the cooling process. The alloy can be effectively protected from oxidation by designing the vacuum degree, the purity of the protective gas, the pressure of the protective gas atmosphere and the melting temperature during the smelting process, and the evaporation of the raw material alloy can be effectively avoided while ensuring that the raw material alloy is fully melted. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 X-ray scanning images of the amorphous composite materials prepared in Example 1 and Comparative Examples 1 to 4 of the present invention.

[0028] Figure 2 This is a microstructure diagram of the amorphous composite material prepared in Example 1 of the present invention;

[0029] Figure 3 This is a diagram of the compressive mechanical properties of the amorphous composite material prepared in Example 1 of the present invention.

[0030] Figure 4 This is a microstructure diagram of the copper-zirconium based amorphous composite material prepared in Comparative Example 1 of the present invention.

[0031] Figure 5 This is a microstructure diagram of the copper-zirconium based amorphous composite material obtained in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0033] The present invention provides a dispersed core-shell hybrid dual-phase reinforced amorphous composite material, the chemical composition expression of which is Zr a Cu b Al c Sn d Ta e, wherein 40≤a≤50, 40≤b≤50, 4≤c≤10, 0.2≤d≤0.8, 3.0≤e≤7.0; and a+b+c+d+e=100; the composite material is a Zr-Cu based amorphous alloy, the reinforcement phase is a Ta-rich phase introduced by the dealloying process and a B2 phase (Ta-rich phase-B2 phase core-shell dual-phase hybrid reinforcement structure) generated in situ with it as the nucleation substrate, and the core-shell dual-phase hybrid structure is uniformly dispersed in the matrix. In order to disperse the hybrid reinforcement phase and ensure that the shell phase (B2 phase) does not undergo martensitic transformation, the present invention designs a preparation process based on the dealloying reaction in the metal melt, successfully refines the precipitation size of the Ta-rich phase, thereby promoting the dispersed distribution of the core-shell hybrid phase, reducing the degree of thermal mismatch between the Ta-rich phase and the B2 phase at the interface, and inhibiting the martensitic transformation of the B2 phase. At the same time, a copper-zirconium-based amorphous matrix containing Sn is selected to improve the thermal stability of the B2 phase, and further avoid the martensitic phase transformation of the B2 phase during the cooling process. The dispersed core-shell hybrid phase reinforced amorphous composite material prepared by the present invention exhibits mechanical properties such as high strength and excellent plastic deformation ability due to the complex deformation stress field distribution brought by the hybrid reinforcement structure and the dispersed distribution characteristics of the hybrid phase itself, and has broad application prospects.

[0034] In a preferred embodiment, the chemical composition expression is Zr a Cu b Al c Sn d Ta e , among which, 42.0≤a≤46.5, 42.0≤b≤46.5, 4.8≤c≤8.2, 0.4≤d≤0.6, 3.0≤e≤7.0; and a+b+c+d+e=100.

[0035] The present invention also provides a method for preparing the dispersed core-shell hybrid dual-phase reinforced amorphous composite material, comprising the following steps:

[0036] S1. According to the atomic percentage in the chemical composition of the amorphous composite material, weigh the corresponding mass of Zr, Ta, Cu, Al and Sn raw materials; mix and melt the Zr and Ta raw materials, and obtain a Zr-Ta pre-alloy after cooling; mix and melt the Cu, Al and Sn raw materials, and obtain a Cu-Al-Sn pre-alloy after cooling;

[0037] S2, mixing the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy and then induction melting to obtain a semi-solid melt, and then casting to obtain a Zr-Cu-Al-Sn-Ta master alloy ingot; wherein, during the melting process, the Cu-Al-Sn pre-alloy will first melt to obtain a Cu-Al-Sn melt, and the Zr-Ta pre-alloy ingot is immersed in the Cu-Al-Sn melt. Since the mixing enthalpy of Ta and the Cu-Al-Sn melt is positive (non-reactive / immiscible), and the mixing enthalpy of Zr and the melt is negative (reactive / miscible), the Zr in the Zr-Ta pre-alloy will undergo a dealloying reaction in the metal melt, selectively dissolve into the Cu-Al-Sn melt, and generate a Zr-Cu-Al-Sn matrix melt, and the remaining Ta forms a dispersed fine Ta phase through surface diffusion;

[0038] S3, spray-casting the master alloy described in step S2 into a copper mold to obtain an amorphous composite material with a matrix of a copper-zirconium-based amorphous alloy and a reinforcement phase of a dispersed core-shell hybrid dual-phase reinforcement structure with a Ta-rich phase-B2 phase.

[0039] The present invention provides a method for preparing a dispersed endogenous core-shell hybrid dual-phase reinforced amorphous composite material, which utilizes the negative mixing enthalpy of the Zr element in the Zr-Ta pre-alloy and the Cu-Al-Sn melt, and is easily dissolved together to obtain the Zr-Cu-Al-Sn target matrix component. At the same time, the high melting point Ta-rich phase (the melting point of Ta is 3017°C) does not react due to the positive mixing enthalpy with the melt, thereby forming a dispersed Ta-rich phase through surface diffusion. In the subsequent cooling process, the Ta-rich phase serves as a heterogeneous nucleation substrate for the B2 phase to form an in-situ self-generated core-shell hybrid dual-phase reinforced structure. There is no oxide layer or interface layer between the dispersed and uniformly distributed in-situ self-generated core-shell hybrid reinforced phase introduced by the present invention and the matrix, which further improves the comprehensive mechanical properties of the composite material.

[0040] In some embodiments, step S1 first mixes the raw materials Zr block, Cu particle, Al particle, Sn particle and Ta particle according to the target atomic ratio, so that the atomic percentage of the target alloy component satisfies the chemical composition Zr a Cu b Al c Sn d Ta e, where 42.0≤a≤46.5, 42.0≤b≤46.5, 4.8≤c≤8.2, 0.4≤d≤0.6, 3.0≤e≤7.0; and a+b+c+d+e=100; under this ratio, the matrix has a high amorphous forming ability, and the B2 phase also has a high phase stability. The purity of the Zr block used in the embodiment of the present invention is above 99.5%. Before batching, the Zr block is mechanically polished to remove the oxide scale to ensure the high purity of each raw material. The purity of Cu, Al, Sn, and Ta particles is above 99.99%.

[0041] In some embodiments, in step S1, the prepared Zr and Ta alloy raw materials are subjected to vacuum arc melting to prepare a Zr-Ta pre-alloyed ingot. Specifically, Zr and Ta in the prepared alloy raw materials are placed in a vacuum arc melting furnace, vacuumed and introduced with a protective gas, and then the alloy raw materials are arc melted. After the melting is completed, the Zr-Ta pre-alloyed ingot is obtained by cooling. During the arc melting, the current is controlled within the range of 20 to 25A, and the arc melting temperature is set to 3200K to 3800K. After cooling, the Zr-Ta pre-alloy is obtained; considering that Ta has a high melting point, a high arc melting temperature can ensure that each component is fully melted. In step S1, the prepared Cu, Al, and Sn alloy raw materials are also subjected to vacuum arc melting to prepare a Cu-Al-Sn pre-alloyed ingot. Specifically, the Cu, Al, and Sn in the prepared alloy raw materials are placed in a vacuum arc melting furnace, vacuumed, and a protective gas is introduced, and then the alloy raw materials are arc melted. After the melting is completed, the Cu-Al-Sn pre-alloyed ingot is cooled to obtain a Cu-Al-Sn pre-alloyed ingot. During arc melting, the current is controlled within the range of 8 to 10A, so that the arc melting Cu-Al-Sn pre-alloy temperature is controlled within 1200K to 1500K. Considering that the boiling point of Sn is relatively low, the low melting temperature can ensure that each component is fully melted and reduce the burning loss of elements. When the above-mentioned pre-alloyed ingot is subjected to vacuum arc melting, the alloy raw materials are co-melted at least 4 times to ensure its chemical uniformity. Each melting is maintained for 3min to 5min after the alloy is completely melted, and then the arc is turned off and the alloy is turned over and melted again after cooling.

[0042] In some embodiments, in step S2, the induction melting to prepare the master alloy is specifically as follows: the Zr-Ta and Cu-Al-Sn pre-alloyed ingots prepared by the arc melting method are broken into small pieces, and are placed together in a boron nitride crucible, and then vacuumed and a protective gas is introduced, and then the metal block is induction heated, and when the metal block is completely melted and kept warm for 2-5 minutes, the crucible is tilted, and the melt is poured into a mold and cooled to obtain the master alloy. In a preferred embodiment, the induction melting temperature is set to 1250K-1500K, and the time is 2-4 minutes; the vacuum degree during induction melting is 3×10 -3 Pa~5×10 -3Pa. The appropriate induction melting temperature (i.e., dealloying reaction temperature) can ensure that the Zr element in the Zr-Ta pre-alloy is completely dissolved into the Cu-Al-Sn melt, while keeping the Ta-rich phase from melting, and forming a fine and dispersed Ta-rich phase through diffusion in the solid state. Experiments have found that when the induction melting temperature is too low, the dealloying reaction is insufficient, Zr cannot be completely stripped from the Zr-Ta pre-alloy solid solution phase, and can only form a large porous Ta-rich phase, and a fine and dispersed Ta-rich phase cannot be obtained. If the induction melting temperature is too high, the Ta-rich phase is easy to aggregate to form a coarse phase, which deteriorates the dispersion distribution effect, causing the interface thermal mismatch problem caused by the coarse Ta-rich phase, and leading to the phase transition from B2 to B19'. At the same time, the experiment also found that excessively high induction melting temperature and / or excessively long dealloying time will cause the melt to absorb more gas elements, causing the matrix composition to deviate from the target composition, resulting in a decrease in the amorphous forming ability of the matrix, and the precipitation of impurity phases during the cooling process. Therefore, in order to prepare a fine, dispersed core-shell hybrid dual-phase reinforced target amorphous composite material in the present invention, it is necessary to control appropriate induction melting or dealloying process conditions.

[0043] In step S3, the amorphous composite material is prepared by vacuum induction copper mold spray casting and melting, specifically: the master alloy is cut into suitable small pieces, placed in a quartz tube with a bottom opening (the aperture is generally 0.8mm to 1.2mm), and a protective gas is introduced into the vacuum chamber after evacuation, the heating system is turned on, and the heating current is slowly adjusted until the master alloy block is completely melted, and an inert gas flow of a preset pressure is applied to the melt to spray the melt into the copper mold below the quartz tube, and the heating system is turned off, and the melt is cooled to room temperature to obtain a copper-zirconium-based amorphous composite material sample. In a preferred embodiment, the preset pressure of the inert gas flow is 0.02MPa to 0.08MPa, so that the melt in the quartz tube fully enters the copper mold before cooling and solidification, so that it is completely filled, and the gas is prevented from being involved in the melt, thereby ensuring that no pore defects will be generated in the sample after solidification.

[0044] In some embodiments, during the arc melting and induction melting, the vacuum degree is 3×10 -3 Pa~5×10 -3 Pa, the protective gas is an inert gas with a purity of 99.999%, such as but not limited to argon, helium, etc., and the atmosphere pressure of the protective gas is -0.05 MPa.

[0045] The present invention utilizes the negative mixing enthalpy of the Zr element in the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy, which is easy to undergo a dealloying reaction in the metal melt and melt and dissolve each other to generate the target component of the amorphous alloy matrix. The high melting point Ta-rich phase (the melting point of Ta is 3017°C) is immiscible with the melt, so it forms a fine dispersed phase through surface diffusion and is distributed in the melt of the amorphous matrix. In the subsequent cooling process, the above-mentioned dispersed Ta-rich phase can serve as a heterogeneous nucleation substrate for another phase, the B2 phase, so that the B2 phase wraps the Ta-rich phase and precipitates, forming an in-situ self-generated core-shell hybrid dual-phase reinforcement structure. At the same time, since the core phase (Ta-rich phase) itself is already finely dispersed, the core-shell dual phase will eventually be refined and evenly distributed, solving the problem of large precipitation size and uneven distribution of the B2 phase. Finally, due to the small size of the Ta-rich phase, the residual heat and thermal stress after cooling are small, and the matrix alloy composition contains Sn, a B2 phase stabilizing element, which avoids the martensitic transformation of the B2 phase to the B19' phase, and obtains the target dual-phase hybrid reinforcement structure. In order to make the Ta-rich phase fine and dispersed, the present invention strictly controls the dealloying reaction time and temperature, because experiments have found that too high a melt temperature or too long a holding time will cause the Ta-rich phase to be coarse, lose its role in promoting the dispersed distribution of the dual-phase structure, and its residual heat and thermal stress will cause the B2 phase to undergo a phase transformation; when the melting temperature is too low or the holding time is too short, the dealloying reaction is incomplete, resulting in a deviation in the Zr element content in the matrix, reducing the amorphous forming ability of the matrix, and at the same time, the Ta-rich phase is partially connected and has poor dispersion, making it difficult to obtain the expected composite structure. The present invention successfully introduces a dispersed in-situ self-generated core-shell hybrid reinforcement phase into the copper-zirconium based amorphous matrix through the above-mentioned component design and process control. Impurity phases such as B19' and other crystallized phases do not exist in the composite structure, and there is no oxide layer or interface layer between the second phase and the matrix, thereby improving the strength and plastic deformation ability of the composite material.

[0046] The above technical solution is described in detail below in conjunction with specific embodiments.

[0047] Example 1

[0048] The Zr prepared in this example 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 (atomic ratio) composite material, specifically comprising the following steps:

[0049] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0050] (2) Place the prepared Zr blocks and Ta particles into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta pre-alloy ingot;

[0051] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain Cu-Al-Sn pre-alloy.

[0052] (4) Zr-Ta and Cu-Al-Sn pre-alloys are placed in a BN crucible together, and then vacuum is evacuated and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1273K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0053] (5) Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The master alloy was crushed, and a master alloy block of appropriate size was selected and placed in a quartz tube crucible with a small hole of 1.0 mm in diameter at the bottom. The induction melting furnace was vacuumed to 3.0×10 -3 Pa, argon gas with a purity of 99.999% was introduced to a relative pressure of -0.05 MPa, and the alloy block was induction melted. After it was fully melted, an argon gas flow with a pressure of 0.04 MPa was introduced into the quartz tube crucible, so that the melt was sprayed into a copper mold with an inner diameter of 2 mm below, and a rod-shaped Zr with a diameter of 2 mm and a length of 60 mm was obtained. 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 Composite materials.

[0054] Figure 1 2 are the XRD diagrams of the embodiments and comparative examples. The XRD diagram corresponding to Embodiment 1 has a diffuse diffraction peak representing the amorphous matrix, and diffraction peaks representing the Ta-rich phase and the B2 phase, but no other diffraction peaks, indicating that under the composition ratio and the dealloying process temperature and time design of Embodiment 1, the martensitic phase transformation of the B2 phase and the precipitation of other crystallized phases are avoided.

[0055] Figure 2 This is a schematic diagram of the microstructure of the copper-zirconium based amorphous composite material obtained in this embodiment. It can be seen that there are only amorphous matrix and Ta-rich phase + B2 phase core-shell mixed reinforcement phase, and the Ta-rich phase is relatively small, with an average size of about 3μm. The fine and dispersed reinforcement phase provides more sites for shear band formation and proliferation. At the same time, the mixed reinforcement structure introduces a more complex deformation stress field distribution, so that the composite material exhibits more excellent mechanical properties.

[0056] Figure 3 This is a diagram of the compressive mechanical properties of the copper-zirconium based amorphous composite material obtained in this embodiment. The fracture stress reaches 2436 MPa, the fracture strain reaches 13.5%, and the plastic strain reaches 11.3%.

[0057] Comparative Example 1

[0058] This comparative example prepared Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The composite material specifically comprises the following steps:

[0059] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0060] (2) Place the prepared Zr blocks and Ta particles into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta pre-alloy ingot;

[0061] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 4 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting 4 times in total, and obtain a Cu-Al-Sn pre-alloyed ingot.

[0062] (4) Zr-Ta and Cu-Al-Sn pre-alloyed ingots are placed in a BN crucible together, and then vacuumed and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1573K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0063] (5) Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The master alloy was crushed, and a master alloy block of appropriate size was selected and placed in a quartz tube crucible with a small hole of 1.0 mm in diameter at the bottom. The induction melting furnace was vacuumed to 3.0×10 -3 Pa, argon gas with a purity of 99.999% was introduced to a relative pressure of -0.05MPa, and the alloy block was induction melted, and the melting temperature was maintained at 900K~1200K. After fully melted, argon gas with a pressure of 0.04MPa was filled into the quartz tube crucible, so that the melt was sprayed into the copper mold with an inner diameter of 2mm below, and a rod-shaped Zr with a diameter of 2mm and a length of 60mm was obtained. 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 Composite materials.

[0064] Figure 1 The XRD diagram of Comparative Example 1 shown is an X-ray scan of the copper-zirconium based amorphous composite material obtained in this comparative example. In addition to the diffraction peaks of the amorphous matrix, Ta-rich phase and B2 phase, there are other diffraction peaks, indicating that the excessively high dealloying temperature introduces other impurity phases.

[0065] Figure 4 This is the microstructure diagram of the copper-zirconium based amorphous composite material obtained in this comparative example. Part of the B2 phase undergoes a martensitic phase transformation, the shell in the core-shell structure is B2+B19', and the Ta-rich phase is relatively coarse, with an average size of about 11μm. The composite material has a fracture stress of 2038MPa, a fracture strain of 3.9%, and a plastic strain of 1.8%.

[0066] Comparative Example 2

[0067] The Zr prepared in this example 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The composite material specifically comprises the following steps:

[0068] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0069] (2) Place the prepared Zr blocks and Ta particles into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta pre-alloy ingot;

[0070] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 4 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting 4 times in total, and obtain a Cu-Al-Sn pre-alloyed ingot.

[0071] (4) Zr-Ta and Cu-Al-Sn pre-alloyed ingots are placed in a BN crucible together, and then vacuumed and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1273K for 5 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0072] (5) Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5The master alloy was crushed, and a master alloy block of appropriate size was selected and placed in a quartz tube crucible with a small hole of 1.0 mm in diameter at the bottom. The induction melting furnace was vacuumed to 3.0×10 -3 Pa, argon gas with a purity of 99.999% was introduced to a relative pressure of -0.05MPa, and the alloy block was induction melted, and the melting temperature was maintained at 900K~1200K. After fully melted, argon gas with a pressure of 0.04MPa was filled into the quartz tube crucible, so that the melt was sprayed into the copper mold with an inner diameter of 2mm below, and a rod-shaped Zr with a diameter of 2mm and a length of 60mm was obtained. 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 Composite materials.

[0073] Figure 1 The XRD diagram of Comparative Example 2 is an X-ray scan of the copper-zirconium based amorphous composite material obtained in this example. In addition to the diffraction peaks of the amorphous matrix, Ta-rich phase and B2 phase, there are other diffraction peaks, indicating that too long dealloying time will also introduce other impurity phases. The composite material has a fracture stress of 2049 MPa, a fracture strain of 3.2%, and a plastic strain of 1.3%.

[0074] Comparative Example 3

[0075] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 43.95 Cu 43.95 Al 7.1 Ta 5 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0076] (2) Place the prepared Zr and Ta blocks into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta master alloy;

[0077] (3) Place the Cu and Al particles in a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.04MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain Cu-Al pre-alloy.

[0078] (4) Zr-Ta and Cu-Al pre-alloys are placed in a BN crucible together, and then vacuum is evacuated and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1273K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0079] (5) Cut the master alloy into appropriate small pieces, put them into a quartz tube with a bottom hole diameter of 0.8 mm, and evacuate to 3×10 -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is -0.04MPa, the heating system is turned on, the heating current is slowly adjusted until the pre-alloyed block is completely melted, and an argon gas flow with a pressure of 0.05MPa is sprayed from above the melt, and the melt is sprayed into a copper mold with an inner diameter of 2mm. The heating system is turned off, and after cooling to room temperature, a 2mm copper-zirconium based amorphous composite material sample is taken out.

[0080] Figure 1 The XRD diagram of Comparative Example 3 is an X-ray scan of the copper-zirconium-based amorphous composite material obtained in this comparative example. In addition to the diffraction peaks of the amorphous matrix, Ta-rich phase and B2 phase, there are other diffraction peaks, indicating that the component system without Sn addition has insufficient amorphous forming ability and poor stability of the B2 phase, and other impurity phases and B19' phases will be introduced. The composite material has a fracture stress of 1928MPa, a fracture strain of 2.6%, and a plastic strain of 0.7%.

[0081] Comparative Example 4

[0082] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 43.45 Cu 43.45 Al 7.1 Sn 1 Ta 5 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0083] (2) Place the prepared Zr and Ta blocks into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta master alloy;

[0084] (3) Place the Cu, Al, and Sn particles in a water-cooled copper mold in a vacuum melting furnace and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.03MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain Cu-Al-Sn pre-alloy.

[0085] (4) Zr-Ta and Cu-Al-Sn pre-alloys are placed in a BN crucible together, and then vacuum is evacuated and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1273K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0086] (5) Cut the master alloy into appropriate small pieces, place them in a quartz tube with a bottom hole diameter of 1.2 mm, and evacuate to 3×10 -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is -0.03MPa, the heating system is turned on, the heating current is slowly adjusted until the pre-alloyed block is completely melted, and an argon gas flow with a pressure of 0.04MPa is sprayed from above the melt, and the melt is sprayed into a copper mold with an inner diameter of 2mm. The heating system is turned off, and after cooling to room temperature, a 2mm copper-zirconium based amorphous composite material sample is taken out.

[0087] Figure 1 The XRD diagram of Comparative Example 4 is an X-ray scan of the copper-zirconium based amorphous composite material obtained in this example. In addition to the diffraction peaks of the amorphous matrix, Ta-rich phase and B2 phase, there are also diffraction peaks of other crystallized phases, indicating that the amorphous forming ability of the component system with excessive Sn addition decreases and other impurity phases are introduced. The composite material has a fracture stress of 1823MPa, a fracture strain of 2.1%, and a plastic strain of ~0.

[0088] Comparative Example 5

[0089] This comparative example prepared Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 (atomic ratio) composite material, specifically comprising the following steps:

[0090] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0091] (2) Place the prepared Zr blocks and Ta particles into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta intermediate pre-alloy;

[0092] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 2 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting 4 times in total, and obtain Cu-Al-Sn pre-alloy.

[0093] (4) Zr-Ta and Cu-Al-Sn pre-alloys are placed in a BN crucible together, and then vacuum is evacuated and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1073K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0094] (5) Zr 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 The master alloy was crushed, and a master alloy block of appropriate size was selected and placed in a quartz tube crucible with a small hole of 1.0 mm in diameter at the bottom. The induction melting furnace was vacuumed to 3.0×10 -3Pa, argon gas with a purity of 99.999% was introduced to a relative pressure of -0.05MPa, and the alloy block was induction melted, and the melting temperature was maintained at 900K~1200K. After fully melted, argon gas with a pressure of 0.04MPa was filled into the quartz tube crucible, so that the melt was sprayed into the copper mold with an inner diameter of 2mm below, and a rod-shaped Zr with a diameter of 2mm and a length of 60mm was obtained. 43.7 Cu 43.7 Al 7.1 Sn 0.5 Ta 5 Composite materials.

[0095] Figure 5 This is the microstructure diagram of the copper-zirconium based amorphous composite material obtained in this comparative example. It can be seen that there are only amorphous matrix and Ta-rich phase + B2 phase core-shell mixed reinforcement phase. However, due to the low dealloying temperature and insufficient dealloying reaction, the Ta-rich phase is not fully diffused and connected to each other. The average size is about 8μm. The fracture stress of the composite material is 2224MPa, the fracture strain is 6.2%, and the plastic strain is 4.3%.

[0096] Example 2

[0097] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 45.7 Cu 45.7 Al 5.2 Sn 0.4 Ta 3.0 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0098] (2) Place the prepared Zr and Ta blocks into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta pre-alloy ingot;

[0099] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.04MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Cu-Al-Sn pre-alloyed ingot.

[0100] (4) Zr-Ta and Cu-Al-Sn pre-alloyed ingots are placed in a BN crucible together, and then vacuum is evacuated and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1373K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0101] (5) Cut the master alloy into appropriate small pieces, put them into a quartz tube with a bottom hole diameter of 0.8 mm, and evacuate to 3×10 -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is -0.04MPa, the heating system is turned on, and the heating current is slowly adjusted until the pre-alloyed block is completely melted. An argon gas flow with a pressure of 0.05MPa is sprayed from above the melt, and the melt is sprayed into a copper mold with an inner diameter of 1mm. The heating system is turned off, and after cooling to room temperature, a copper-zirconium-based amorphous composite material sample with a diameter of 1mm is taken out.

[0102] The core-shell dual-phase reinforced amorphous composite material obtained in this example consists of an amorphous matrix and a fine dispersed Ta-rich phase + B2 phase core-shell mixed reinforcement phase. The average size of the Ta-rich phase is about 3μm. The compressive fracture stress of the composite material reaches 2216MPa, the fracture strain reaches 7.7%, and the plastic strain reaches 5.9%.

[0103] Example 3

[0104] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 44.2 Cu 44.2 Al 8.0 Sn 0.6 Ta 3.0 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0105] (2) Place the prepared Zr and Ta blocks into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta master alloy;

[0106] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.03MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain Cu-Al-Sn pre-alloy.

[0107] (4) Zr-Ta and Cu-Al-Sn pre-alloys are placed in a BN crucible together, and then vacuum is evacuated and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1423K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0108] (5) Cut the master alloy into appropriate small pieces, place them in a quartz tube with a bottom hole diameter of 1.2 mm, and evacuate to 3×10 -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is -0.03MPa, the heating system is turned on, and the heating current is slowly adjusted until the pre-alloyed block is completely melted. An argon gas flow with a pressure of 0.04MPa is sprayed from above the melt, and the melt is sprayed into a copper mold with an inner diameter of 3mm. The heating system is turned off, and after cooling to room temperature, a 3mm copper-zirconium-based amorphous composite material sample is taken out.

[0109] The hybrid dual-phase reinforced amorphous composite material obtained in this example consists of an amorphous matrix and a fine dispersed Ta-rich phase + B2 phase core-shell hybrid reinforcement phase. The average size of the Ta-rich phase is about 3μm. After testing, the compressive fracture stress reaches 2254MPa, the fracture strain reaches 7.5%, and the plastic strain reaches 5.8%.

[0110] Example 4

[0111] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 44.6 Cu 44.38 Al 6.8 Sn 0.42 Ta 3.8The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0112] (2) Place the prepared Zr and Ta blocks into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta pre-alloy ingot;

[0113] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.04MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Cu-Al-Sn pre-alloyed ingot.

[0114] (4) Zr-Ta and Cu-Al-Sn pre-alloyed ingots are placed in a BN crucible together, and then vacuumed and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1398K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0115] (5) Cut the master alloy into appropriate small pieces, place them in a quartz tube with a bottom hole diameter of 1.0 mm, and evacuate to 3×10 -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is -0.04MPa, the heating system is turned on, and the heating current is slowly adjusted until the pre-alloyed block is completely melted. An argon gas flow with a pressure of 0.05MPa is sprayed from above the melt, and the melt is sprayed into a copper mold with an inner diameter of 1mm. The heating system is turned off, and after cooling to room temperature, a copper-zirconium-based amorphous composite material sample with a diameter of 1mm is taken out.

[0116] The core-shell dual-phase reinforced amorphous composite material obtained in this example consists of an amorphous matrix and a fine dispersed Ta-rich phase + B2 phase core-shell mixed reinforcement phase. The average size of the Ta-rich phase is about 3.2μm. The compressive fracture stress of the composite material reaches 2289MPa, the fracture strain reaches 8.6%, and the plastic strain reaches 6.7%.

[0117] Example 5

[0118] (1) The alloy raw material is mechanically polished to remove the oxide scale, and then ultrasonically cleaned in anhydrous ethanol. After drying, Zr 42.7 Cu 43.9 Al 6.7 Sn 0.5 Ta 6.2 The atomic percentage of the alloy is converted into mass percentage, and the corresponding Cu particles, Al particles, Sn particles, Ta particles and Zr blocks are weighed and configured according to a total mass of about 80 g.

[0119] (2) Place the prepared Zr and Ta blocks into a water-cooled copper mold in a vacuum melting furnace and draw vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.05MPa, perform arc melting on the raw materials, control the current to 22A, control the melting temperature to be within the range of 3200K to 3800K, and after fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain a Zr-Ta master alloy;

[0120] (3) Place Cu particles, Al particles, and Sn particles in a water-cooled copper mold in a vacuum melting furnace, and draw a vacuum to 3.0×10 -3 Pa, introduce argon gas with a purity of 99.999% to a relative pressure of -0.03MPa, arc melt the raw materials, control the current to 10A, and control the melting temperature within the range of 1200K to 1500K. After fully melting for 3 minutes, stop melting, turn the alloy ingot over with a turning rod, repeat melting for a total of 4 times to obtain Cu-Al-Sn pre-alloy.

[0121] (4) Zr-Ta and Cu-Al-Sn pre-alloys are placed in a BN crucible together, and then vacuum is evacuated and protective gas is introduced. The metal block is then induction heated. After the metal block is completely melted, it is kept at 1468K for 3 minutes, and then the crucible is tilted. The melt is poured into a mold and cooled to obtain a master alloy.

[0122] (5) Cut the master alloy into appropriate small pieces, place them in a quartz tube with a bottom hole diameter of 1.2 mm, and evacuate to 3×10 -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is -0.05MPa, the heating system is turned on, and the heating current is slowly adjusted until the pre-alloyed block is completely melted. An argon gas flow with a pressure of 0.04MPa is sprayed from above the melt, and the melt is sprayed into a copper mold with an inner diameter of 2mm. The heating system is turned off, and after cooling to room temperature, a 2mm copper-zirconium based amorphous composite material sample is taken out.

[0123] The hybrid dual-phase reinforced amorphous composite material obtained in this example consists of an amorphous matrix and a fine dispersed Ta-rich phase + B2 phase core-shell hybrid reinforcement phase. The average size of the Ta-rich phase is about 3.8μm. The tested compressive fracture stress reaches 2379MPa, the fracture strain reaches 11.8%, and the plastic strain reaches 9.7%.

[0124] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A dispersed core-shell hybrid dual-phase reinforced amorphous composite material, characterized in that: Its chemical composition expression is Zr a Cu b Al c Sn d Ta e , Among them, 40≤a≤50, 40≤b≤50, 4≤c≤10, 0.2≤d≤0.8, 3.0≤e≤7.0; and a+b+c+d+e=100; The matrix of the composite material is a copper-zirconium-based amorphous alloy, and the reinforcement phase is a hybrid dual phase with a core-shell structure, wherein the core phase in the hybrid dual phase with the core-shell structure is a dispersed Ta-rich phase, and the shell phase is a B2 phase generated around the Ta-rich phase, and the hybrid dual phase with the core-shell structure is dispersed in the matrix; The method for preparing the dispersed core-shell hybrid dual-phase reinforced amorphous composite material comprises the following steps: S1. According to the atomic percentage in the chemical composition of the amorphous composite material, weigh the corresponding mass of Zr, Ta, Cu, Al and Sn raw materials; mix and melt the Zr and Ta raw materials, and obtain a Zr-Ta pre-alloy after cooling; mix and melt the Cu, Al and Sn raw materials, and obtain a Cu-Al-Sn pre-alloy after cooling; S2, mixing the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy and then induction melting to obtain a semi-solid melt, and then casting to obtain a Zr-Cu-Al-Sn-Ta master alloy ingot; S3, spray-casting the master alloy in step S2 into a copper mold to obtain an amorphous composite material with a matrix of a copper-zirconium-based amorphous alloy and a reinforcement phase of a dispersed core-shell hybrid dual-phase reinforcement structure of a Ta-rich phase-B2 phase; Wherein, in step S2, the specific operation of the induction melting is: putting the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy into a ceramic crucible at the same time, performing vacuum induction melting, and pouring the final melt into a mold by tilt casting to obtain a master alloy; the temperature of the vacuum induction melting is 1250K to 1500K, and the time is 2 to 4 minutes; During the induction melting process described in step S2, the Cu-Al-Sn pre-alloy will first melt to obtain a Cu-Al-Sn melt, and the Zr-Ta pre-alloy ingot will be immersed in the Cu-Al-Sn melt. Since the mixing enthalpy of Ta and the Cu-Al-Sn melt is positive, and the mixing enthalpy of Zr and the melt is negative, the Zr in the Zr-Ta pre-alloy will undergo a dealloying reaction in the metal melt and selectively dissolve into the Cu-Al-Sn melt to generate a Zr-Cu-Al-Sn matrix melt, the composition of which is the same as the target melt composition, and the B2 phase can be precipitated in situ during the spray casting process described in step S3; at the same time, the remaining Ta in the Zr-Ta pre-alloy can form a dispersed and fine Ta phase through surface diffusion.

2. The amorphous composite material according to claim 1, characterized in that: Its chemical composition expression is Zr a Cu b Al c Sn d Ta e , among which, 42.0≤a≤46.5, 42.0≤b≤46.5, 4.8≤c≤8.2, 0.4≤d≤0.6, 3.0≤e≤7.0; and a+b+c+d+e=100.

3. The method for preparing the dispersed core-shell hybrid dual-phase reinforced amorphous composite material according to any one of claims 1 or 2, characterized in that: The steps include: S1. According to the atomic percentage in the chemical composition of the amorphous composite material, weigh the corresponding mass of Zr, Ta, Cu, Al and Sn raw materials; mix and melt the Zr and Ta raw materials, and obtain a Zr-Ta pre-alloy after cooling; mix and melt the Cu, Al and Sn raw materials, and obtain a Cu-Al-Sn pre-alloy after cooling; S2, mixing the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy and then induction melting to obtain a semi-solid melt, and then casting to obtain a Zr-Cu-Al-Sn-Ta master alloy ingot; S3, spray-casting the master alloy in step S2 into a copper mold to obtain an amorphous composite material with a matrix of a copper-zirconium-based amorphous alloy and a reinforcement phase of a dispersed core-shell hybrid dual-phase reinforcement structure of a Ta-rich phase-B2 phase; Wherein, in step S2, the specific operation of the induction melting is: putting the Zr-Ta pre-alloy and the Cu-Al-Sn pre-alloy into a ceramic crucible at the same time, performing vacuum induction melting, and pouring the final melt into a mold by tilt casting to obtain a master alloy; the temperature of the vacuum induction melting is 1250K to 1500K, and the time is 2 to 4 minutes; During the induction melting process described in step S2, the Cu-Al-Sn pre-alloy will first melt to obtain a Cu-Al-Sn melt, and the Zr-Ta pre-alloy ingot will be immersed in the Cu-Al-Sn melt. Since the mixing enthalpy of Ta and the Cu-Al-Sn melt is positive, and the mixing enthalpy of Zr and the melt is negative, the Zr in the Zr-Ta pre-alloy will undergo a dealloying reaction in the metal melt and selectively dissolve into the Cu-Al-Sn melt to generate a Zr-Cu-Al-Sn matrix melt, the composition of which is the same as the target melt composition, and the B2 phase can be precipitated in situ during the spray casting process described in step S3; at the same time, the remaining Ta in the Zr-Ta pre-alloy can form a dispersed and fine Ta phase through surface diffusion.

4. The preparation method according to claim 3, characterized in that: In step S1, Zr and Ta raw materials are mixed and then subjected to vacuum arc melting, and Zr-Ta pre-alloy is obtained after cooling; Cu, Al and Sn raw materials are mixed and then subjected to vacuum arc melting, and Cu-Al-Sn pre-alloy is obtained after cooling.

5. The preparation method according to claim 4, characterized in that: The Zr and Ta raw materials are mixed and then subjected to vacuum arc melting at a temperature of 3200K to 3800K; the Cu, Al and Sn raw materials are mixed and then subjected to vacuum arc melting at a temperature of 1200K to 1500K.

6. The preparation method according to claim 4, characterized in that: When vacuum melting Zr, Ta raw materials and Cu, Al, Sn raw materials are respectively carried out, the vacuum arc melting process is repeated at least 4 times, each melting is maintained for 3min to 5min after the charge is completely melted, and then the alloy is turned over after cooling for the next melting.

7. The preparation method according to claim 3, characterized in that: The vacuum degree during vacuum induction melting is 3×10 - 3 Pa~5×10 -3 Pa.

8. The preparation method according to claim 3, characterized in that: Step S3 specifically includes: crushing the Zr-Cu-Al-Sn-Ta master alloy ingot and placing it into a quartz tube for spray casting, performing vacuum induction melting, and spray casting the melted material through a copper mold to obtain a copper-zirconium based amorphous composite material.

Citation Information

Patent Citations

  • Mixed phase reinforced zirconium-based amorphous composite material and preparation method thereof

    CN113322422A